2006
DOI: 10.1016/j.chembiol.2005.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Carbamylation on Type I Collagen Conformational Structure and Its Ability to Activate Human Polymorphonuclear Neutrophils

Abstract: Carbamylation by urea-derived cyanate is a posttranslational modification of proteins increasing during chronic renal insufficiency, which alters structural and functional properties of proteins and modifies their interactions with cells. We report here the major structural alterations of type I collagen induced by carbamylation. Biophysical methods revealed that carbamylated collagen retained its triple-helical structure, but that slight changes destabilized some regions within the triple helix and decreased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
101
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(111 citation statements)
references
References 42 publications
7
101
0
3
Order By: Relevance
“…Indeed, using methylglyoxal as glycating agent, it has been demonstrated that arginine within the RGD collagen binding sites, preferentially reacts with this compound and consequently affect HT1080 cell adhesion and spreading (23). Concerning carbamylation, its minor impact on tumor cell migration is in agreement with the capacity of this modified collagen to retain its triple helical structure as recently demonstrated by our laboratory using Raman microspectroscopy (31).…”
Section: Discussionsupporting
confidence: 63%
“…Indeed, using methylglyoxal as glycating agent, it has been demonstrated that arginine within the RGD collagen binding sites, preferentially reacts with this compound and consequently affect HT1080 cell adhesion and spreading (23). Concerning carbamylation, its minor impact on tumor cell migration is in agreement with the capacity of this modified collagen to retain its triple helical structure as recently demonstrated by our laboratory using Raman microspectroscopy (31).…”
Section: Discussionsupporting
confidence: 63%
“…It has been shown that glycoxidation rate increased as a function of age in skin collagen of various mammalian species or cartilage collagen in humans, potentially contributing to age-related impairments (11,34,41). However, other biochemical reactions are involved in molecular aging, such as carbamylation, which is caused by the reaction of proteins with isocyanic acid (4,(42)(43)(44)(45). Isocyanic acid is mainly derived from urea dissociation but may also be generated from thiocyanate metabolism or brought by environment (15,19,23).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that the modification of only four HCit residues per α-chain is sufficient to induce local destabilization, leading to a decrease of thermal stability, or fibrillogenesis impairment or alter sensitivity to proteolysis by matrix metalloproteinases (42,43). In addition, collagen carbamylation leads to functional damages, because carbamylated collagen is able to alter oxidative functions of inflammatory cells (42).…”
Section: Discussionmentioning
confidence: 99%
“…A prior study of collagen carbamylation indicated that destabilization of the triple helix is a contributor to relative MMP activity. Carbamylation of 11 Lys residues in type I collagen leads to a decrease in triple-helix stability (ϳ2°C) (63). Although the Lys residues most susceptible to carbamylation are distant from the actual MMP cleavage site (63), carbamylation results in an increase in MMP-2 activity (64).…”
Section: Nomentioning
confidence: 99%
“…Carbamylation of 11 Lys residues in type I collagen leads to a decrease in triple-helix stability (ϳ2°C) (63). Although the Lys residues most susceptible to carbamylation are distant from the actual MMP cleavage site (63), carbamylation results in an increase in MMP-2 activity (64). Thus, destabilization of the triple helix increases MMP-2 activity, which is analogous to what was observed in the present study.…”
Section: Nomentioning
confidence: 99%